Pengaruh pelatihan pemeliharaan kesehatan gigi pada guru sekolah dasar sistem full day terhadap perubahan status kebersihan mulut siswa - Anne Agustina Suwargiani; Riana Wardani; Netty Suryanti; Asty Samiaty Setiawan (Majalah Kedokteran Gigi Indonesia, 2017)
Effect of dental care training on primary full day school teachers towards student’s oral hygiene status alteration. Elementary School age is the most appropriate age of having proper toothbrush technique teaching, because at this age children are entering mixed dentition period, so they should be able to do proper toothbrush technique. The practice of brushing teeth in full-day system elementary school is fundamental because most of the student’s time was spent in school, and they were also having lunch there, so the students should have been able to maintain the health of their teeth, which can only be implied with active role of teachers. The objective of this study was to analyze the effect of dental care training towards student’s oral hygiene status alteration. The method of this research was mixed methods that consisted of quantitative research phase that was done by providing questionnaires about knowledge, attitudes and behaviours of teachers after toothbrushing training, and the student’s toothbrushing skill that was measured through the oral hygiene status (OHIS green Vermillion). Whilst the phase of qualitative research was done by observation using observation checklist to identied the inhibiting factors of delivering the training results to the students. The sampling technique was total sampling, with all the teachers were taken as samples. The results from linear regression test showed that there was a moderate relation between the training effect towards student’s oral hygiene status alteration (R : 0.43). The contribution percentage of teacher’s knowledge, attitude and action variable used in the research model was seen on R square value that was 18.5%, whilst on the value of 81.5% was inuenced by other variables not included in the research. This value was the result of students’ variety perceptions about toothbrushing; the unconducive situation of the classrooms; difculties of teachers to delivered the counselling materials; teacher’s feeling of knowledge limitations; and forgetfulness of the usage of the dental model replica. There was a signicant effect of the action towards the oral hygiene status of the students, but there was no signicant inuence of knowledge and attitude towards the oral hygiene status of the students. Conclusions: Dental care training on full-day primary school teachers did not signicantly change their knowledge and attitude of toothbrushing, but continuous and proper practice after training, however, gave signicant effect on student’s oral hygiene status. Inhibiting factors of alteration were coming from internal environment of both teachers and students, and also due to lack of facilities. ABSTRAKUsia Sekolah Dasar merupakan usia yang tepat untuk mengajarkan teknik menyikat gigi  yang  baik  dan  benar, karena pada usia ini anak sedang dalam memasuki periode gigi campuran  dan sudah harus mampu menyikat  gigi baik dan benar. Penerapan penyikatan gigi di Sekolah Dasar dengan sistem full day sangat diperlukan, mengingat waktu anak di sekolah lebih lama dan melewati waktu makan siang sehingga anak harus mampu menjaga kesehatan giginya sendiri. Penerapan tersebut sangat membutuhkan peran guru. Tujuan penelitian yaitu menganalisis pengaruh pelatihan penyikatan gigi pada guru terhadap status kebersihan mulut siswa. Mixed methode terdiri dari tahap penelitian kuantitatif dengan pemberian kuisioner pengetahuan, sikap dan tindakan guru setelah pelatihan penyikatan gigi dan keterampilan menyikat gigi siswa diukur melalui status kebersihan mulut (OHIS green Vermillion) dan tahap penelitian kualitatif dengan melakukan observasi menggunakan cek list observasi untuk mengetahui faktor penghambat transfer hasil pelatihan pada siswa. Metode penelitian deskriptif analitik. Sampel penelitian diambil dari seluruh populasi, dimana semua guru diambil sebagai sampel penelitian. Hasil penelitian melalui uji korelasi linier menunjukkan hubungan antara pengetahuan, sikap dan tindakan terhadap status kebersihan gigi dan mulut adalah sedang (R:0.43). Prosentase sumbangan variabel pengetahuan, sikap dan tindakan guru yang digunakan dalam model terlihat pada nilai R square yaitu sebesar 18,5%, sedangkan sisanya sebesar 81,5% dipengaruhi oleh variabel lain yang tidak dimasukkan ke dalam penelitian. ada pengaruh signikan tindakan terhadap status kebersihan mulut siswa, namun tidak ada pengaruh secara signikan pengetahuan dan sikap terhadap status kebersihan mulut siswa. Faktor internal guru dan siswa serta faktor eksternal berupa penyediaan fasilitas. Simpulan penelitian mixed methode ini adalah pelatihan penyikatan gigi pada guru sekolah dasar sistem full day berpengaruh sebesar 18,5%, terhadap status kebersihan mulut siswa. Faktor penghambat menerapkan hasil pelatihan yaitu faktor internal dan eksternal guru dan siswa.